Você consegue!: linguagem e persistência em crianças de idade escolar - Borges, Luana Barretto (Universidade Federal de São Carlos, 2024)
From a very young age, infants are exposed to new and challenging situations, but when they are faced with everyday challenges, they need to be persistent. Studies have shown that individual differences in persistence emerge as young as 18 months of age and can predict academic performance and motivation years later. Furthermore, recent research has demonstrated a relationship between the type of language to which infants and children are exposed (e.g., praise that values ​​effort vs. praise for children's characteristics) and their individual persistence in challenging situations. However, as far as we know, there are no studies testing possible relations between the language used by children and their level of persistence. The present research therefore had two main goals: a) to investigate whether children aged 7 to 8 use language related to persistence, process praise and personal praise during the narration of a book without words (which presents several challenging situations for the character); and b) test a possible relationship between the type of language used by children during the book narration and performance in a persistence task. In this task, children were asked to solve a problem (e.g., opening a box that contains a toy, but which is very difficult to open) and the time during which the child persisted in the challenge was measured. The final sample consisted of 44 participants (Mage = 89 months, SD = 3.75 months). The results indicated that 90.9% of the children used words related to persistence during the narrative (e.g., "try"; "train"), and 40.9% presented messages encouraging persistence (e.g., "You have to train hard to achieve something"). Thus, it can be concluded that Brazilian children aged 7 to 8 years use language related to persistence. The sample was divided into High Persistence and Medium Persistence groups, using 240-second in the PT as the cutoff score. A significant and moderate Spearman correlation was found between the presence of messages encouraging persistence in the narrative and the time during which children persisted in the PT (r = 0.504, p = 0.003) in the Medium Persistence group.
You can do it! language and persistence in school aged children
Keywords: Persistência; Linguagem; Crianças; Desenvolvimento infantil; Persistence; Language; Children; Child development; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO